Burosumab in management of X-linked hypophosphataemia: a retrospective cohort study of growth and serum phosphate levels. Issue 5 (30th January 2023) - Walker, Emma Yi Xiu; Lindsay, Timothy Alexander James; Allgrove, Jeremy; Marlais, Matko; Bockenhauer, Detlef; Hayes, Wesley
Abstract : Background: Burosumab, an antifibroblast growth factor 23 monoclonal antibody, improves rickets severity, symptoms and growth in children with X-linked hypophosphataemia (XLH) followed up to 64 weeks in clinical trials. International dosing guidance recommends targeting normal serum phosphate concentration; however, some children may not achieve this despite maximal dosing. This study compares clinical outcomes in children with XLH on long-term burosumab treatment who achieved normal phosphate versus those who did not. Methods: Single-centre retrospective review of a large paediatric cohort with XLH treated with burosumab. We evaluated growth and biochemical markers of bone health in those who did compared with those who did not achieve normal plasma phosphate concentration. Results: Fifty-five children with XLH with median age of 11.7 (IQR 6.8–15.5) years were included. 27 (49%) had low plasma phosphate concentration, and 27 (49%) had normal phosphate after a median burosumab treatment duration of 3.3 (IQR 2.6–3.7) years. 1 (2%) did not have a recent phosphate level recorded. No difference in growth was found between normal and abnormal phosphate groups (p=0.9). Conclusions: Young children with XLH experience sustained growth on long-term burosumab treatment, although without normal plasma phosphate concentration in many. Consideration should be made to changing burosumab dosing recommendations to target normalisation of alkaline phosphatase, as opposed to plasma phosphate concentration.